River Scene, Trinidad - (:unkn) unknown (Davidson and Todd, [Trinidad and Tobago], 2011)
The postcard shows an idyllic river scene.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; [1920]; Scenic byways--Trinidad and Tobago; Landscapes--Trinidad and Tobago; Scenes--Trinidad and Tobago; Rivers--Trinidad and Tobago; Rocks--Trinidad and Tobago; Boulders--Trinidad and Tobago; Trees--Trinidad and Tobago; Riparian areas--Trinidad and Tobago